Geologia, geocronologia U-PB e SM-ND e petrologia do Migmatito Furna Azul : implicações sobre a evolução crustal mesoproterozoica da Orogenia San Ignácio – SW do Cráton Amazônico - Nascimento, Newton Diego Couto do (2015)
The Migmatite Furna Azul was first described as a banded orthogneiss of tonalitic to granodioritic belonging to Intrusive Suite Serra do Bau correlate the Gneiss Complex Chiquitanía described in Bolivia. Petrographic and structural features to classify the migmatite as transitional metatexites, being possible to distinguish rich facies melanosome from another leucosome. Amphibolites enclaves and dioritics injections occur frequently. The essential paragenesis of metatexites consists of quartz, plagioclase, alkali feldspar, biotite and garnet, which are oriented forming hololeucocratics levels and mesocratic of melanosome and leucosome interspersed. The enclaves are made up of brown hornblende, plagioclase, quartz and clinopyroxene distributed in concordants bands with the structure of metatexites. This mineral assemblage, although not diagnostic, indicates a high peak metamorphic in the amphibolite facies. The diorites injections are composed of plagioclase, alkali feldspar and quartz (<13%) and commonly biotite, garnet, epidote and monazite as accessories. In terms of evolution of deformation note that the metatexites and enclaves were intensely deformed, while injections are slightly foliated, probably the sin and tardi cinematic. The geochemical pattern suggests a crustal evolution in two stages, first there was the formation of the protolith in 1.43 Ga, early to Orogeny San Ignacio, from the reworking of a orosirian crust (1.9 Ga). In an interval of 100,000 years, was the average degree of metamorphism responsible for crustal melting and forming of metatexites during the collisional stage of orogeny San Ignacio, also evidenced by the generation of migmatites of typical structures associated with crystallization of dioritics injections around 1.34 Ga, from the melting of the continental crust younger extracted from the mantle at 1.47 Ga.